PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI PENGGUNA APLIKASI PENYEDIA JASA LAYANAN PUBLIK PEDULILINDUNGI - Pangaribuan, Thania Theresia; Hulman Panjaitan; Tomson Situmeang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
In the midst of the current Covid-19 pandemic, all countries including Indonesia are looking for many efforts to suppress the spread of the COVID-19 virus, one of the efforts that have been made by the Government of Indonesia is to create the PeduliLindung application. In the PeduliLindung application, the public will be asked for data in the form of Full Name, Population Identification Number (NIK), and Telephone Number. The PeduliLindungi application can be used if the public has provided their personal data. The PeduliLindung application will provide facilities in the form of providing online certificates and application users will be given information regarding the locations they want to visit to avoid crowds so that the spread of COVID-19 can be minimized. However, behind the convenience provided by the government through the PeduliLindung application, this has not been able to guarantee the security of the public's personal data when using the PeduliLindugi application. The research method that the author uses is a normative juridical research with a statutory approach. In research using this method, the authors analyze the legal protection for public personal data when using the PeduliLindungi public service provider application and what the legal liability of service providers will be if the public's personal data is leaked. The results of the research that the authors obtained in conducting the research are that the Legal Protection of PeduliLindung application users in this case regarding the public's Personal Data can be reviewed based on the Agreement (Terms and Conditions contained in the application) and based on the provisions of the legislation in force in Indonesia. In the event that the PeduliLindugi public service provider fails to ensure the security of the public's personal data, the responsibility of the service provider can be reviewed from the Consumer Protection Law, PP PSTE, Permenkominfo, ITE Law and the law on Public Services